Association between anatomical distribution of symptomatic peripheral artery disease and cerebrovascular disease. (June 2020) - Virtanen, Juha; Varpela, Markus; Biancari, Fausto; Jalkanen, Juho; Hakovirta, Harri
Aim: Peripheral arterial disease is frequently associated with significant atherosclerosis of other vascular beds. The aim of the present study was to investigate a possible association between peripheral arterial disease segment-specific disease burden and cerebrovascular disease. Methods: Two-hundred and twenty-six patients with clinically symptomatic peripheral arterial disease from the prospective PureASO registry were followed up after revascularization. The breadth of peripheral arterial disease was quantified at the time patients entered the study. The segment-specific peripheral arterial disease burden was correlated to cerebrovascular disease and imaging findings during a five-year follow-up. Results: At five years, cerebrovascular disease-free survival after lower limb revascularization was 31%. Patients with peripheral arterial disease involving the crural arteries had significantly more ischemic degenerative changes at brain imaging ( p  = 0.031), whereas patients with aorto-iliac and femoropopliteal segment peripheral arterial disease had more significant (>50% uni- or bilaterally) internal carotid artery stenosis compared to patients with crural peripheral arterial disease ( p  = 0.006). According to Cox regression analyses, crural arteries burden was associated with a significantly increased risk of mortality (adjusted HR 2.07, CI 95% 1.12–3.28, p  = 0.021) and cerebrovascular events (adjusted HR 1.97, CI 95% 1.19–3.26, p  = 0.008). Conclusions: Present results suggest that atherosclerosis burden at different lower limb artery segments is associated with defined cerebrovascular disease. This further suggests that risk factors and pathophysiological mechanisms are congruent across particular vascular beds.